Thomas Hobbes y Sigmund Freud: pensadores del (des)orden - Ariana, Reano (Foro Interno, 2009)
This paper traces how two authors from seemingly different theoretical fields address the tragedy of Modernity in similar ways. The concept of tragedy indicates that the order of the world is no longer pre-determined by a divine will, but is instead the outcome of human action. To illustrate this point, Thomas Hobbes’ natural condition and Sigmund Freud’s primal horde will be revisited to examine the contingent character of that which is human. Following these two perspectives this paper will account for the notion of order as required —though impossible— social production. In Freud’s work this notion stems from the idea of Kultur whereas Hobbes connects it to the Leviathan itself. According to both theoretical perspectives the State and Culture constitute social artifacts intended to put in order the constitutive disorder of Society.
Keywords: Order; Disorder; Tragedy; Law; Leviathan; Kultur